Rockburst risk assessment in deep mining using ensemble models with Interpretable features - Jiachuang Wang; Xiaofeng Huang; Longjun Dong; Shengyu Ji; Caiyan Luo (Tunnelling and Underground Space Technology, 2026)

Sustainable recycling of mining waste: A bibliometric analysis of global research trends over the past 26 years - Hongwei Wang; Kaifeng Xu; Longjun Dong; Daoyuan Sun; Fang Yan (Journal of Environmental Chemical Engineering, 2026)

Antibacterial mechanisms of magnolol against Streptococcus agalactiae and immunomodulatory effects in Schizothorax prenanti - Yilin Wang; Kun Peng; Longjun Deng; Yihao Wang; Qibin Jiang; Tiancai Li; Ping Ouyang; Defang Chen; Xiaoli Huang; Yi Geng (Fish & Shellfish Immunology, 2026)

Myostatin in fish: current understanding of its characterization, function, and signaling pathways - Yujun Wang; Longjun Deng; Tiancai Li; Li Liu; Dongjie Wang; Wei Luo; Zongjun Du (Fish Physiology and Biochemistry, 2026)

Genome-Guided Probiotic Mechanisms of Enterococcus hirae SMU2502: Wnt/β-catenin-Driven Intestinal Epithelial Proliferation and Protection Against Salmonella Infection - Longjun Ran; Danni Wang; Haojinming Tang; Ganlin Wang; Wenzhu Salang; Falong Yang; Huanrong Zhang; Haifeng Liu; Shiwen Xu; Dechun Chen (Probiotics and Antimicrobial Proteins, 2026)

The increasing impact of vegetation productivity on global wetland methane emissions - Longjun Wang; Peng Li; Qiuan Zhu; Xiaolu Zhou; Zhengmiao Deng; Zelin Liu; Ziying Zou; Changhui Peng (Global and Planetary Change, 2026)

Life-cycle regulation of carbohydrate metabolism revealed by glucokinase (gck) in two cyprinids, Spinibarbus denticulatus and Schizothorax prenanti - Yongyao Guo; Yue Zhang; Tiancai Li; Longjun Deng; Zhonggang Guo; Li Liu; Pengyu Chen; Luojia Li; Wei Luo; Dongjie Wang; Zongjun Du (Aquaculture, 2026)

Advances and challenges in the valorization of mine tailing wastes as sustainable geopolymers: a bibliometric analysis from circular economy perspective since the 21st century - Hongwei Wang; Kaifeng Xu; Longjun Dong; Daoyuan Sun (Minerals Engineering, 2026)

Photothermal-enhanced capillary/siphon-driven self-priming pump for highly efficient recovery of various oils - Feilong Liu; Linlin Yan; Yingjie Zhang; Jun Ma; Pengcheng Liu; Longjun Wang; Da long Li; Xiquan Cheng (Journal of Hazardous Materials, 2026)

Research on microseismic parameter prediction for rock mass instability disasters based on time series models - Longjun Dong; Xiaofeng Huang; Shenglan Li; Jiachuang Wang (Journal of Applied Geophysics, 2026)

Electro-chemo-mechanically stable semi-interpenetrating interphase customization for prolonged Zn metal anodes - Jianhui Zhu; LongJun He; Jianbin Ruan; Hongying Li; Chenglong Xu; Ming Yang; Guomin Li; Yanyi Wang; Jingting Luo; Jinlai Zhao; Dingtao Ma; Peixin Zhang (Chemical Engineering Journal, 2026)

Degradable Janus structured micro-nano fibrous membranes for effective particle filtration and antibacterial activity in high humidity working conditions - Gang Zhou; Zhuo Xu; Gang Li; Longjun Wang; Heng Sun; Mingyu Zhang; Yueying Xin; Yongmei Wang (Chemical Engineering Journal, 2026)

Basalt fiber-reinforced solid waste-based binder treated high-moisture dredged sediment: engineering performance, micro-mechanisms, and environmental impact - Hongwei Wang; Jiahui Zhang; Longjun Dong; Dongxing Wang; Daoyuan Sun; Chao Huang (Journal of Soils and Sediments, 2026)

Wake-induced vibration of a downstream cylinder in tandem configurations: an activation-modulation framework - Qiuying Li; Guanghao Chen; Nan Jiang; Jinhui Yue; Longjun Wang; Jian Liu (Ocean Engineering, 2026)

Presymbiotic activation of karrikin signaling creates a permissive state for arbuscular mycorrhizal symbiosis by derepressing the NSP1–NSP2–SLR1 transcriptional complex in rice - Kai Hong; Xueying Yang; Yiqing Tan; Yonggang Liu; Qianwei Xia; Longjun Zeng; Linyuan Zou; Ke Wan; Ya Zhang; Shujing Kang; Tao Huang; Wanqing Lv; et al. (Molecular Plant, 2026)

Global trends and perspectives in soil stabilization/solidification technologies: A three-decade bibliometric analysis focused on heavy metal remediation and sustainable applications - Hongwei Wang; Kaifeng Xu; Longjun Dong; Daoyuan Sun (Journal of Environmental Chemical Engineering, 2026)

Measurement and Impact Mechanism of Carbon Costs in China’s Industrial Enterprises - Liping Wang; Longjun Chen; Panpan Gao; Chuang Li (Environmental Modeling & Assessment, 2026)

Ammonia nitrogen accumulation and metabolic regulation in large-scale loach (Paramisgurnus dabryanus) exposed to sub-chronic carbonate alkalinity: Insights from biochemical and omics analyses - Wei Luo; Luojia Li; Li Liu; Yujun Wang; Longjun Deng; Tiancai Li; Dongjie Wang; Zongjun Du (Aquaculture, 2026)

Numerical analysis of anti-dislocation performance in cross-fault tunnels based on cohesive elements - Heng Zhang; Jie Wang; Longjun Xu; Chaoyue Jin; Hao Tian; Jiale Liu; Lili Xie (Computers and Geotechnics, 2026)

New conditional ground motion model for permanent displacement in near-fault zones - Longjun Xu; Hao Tian; Chaoyue Jin; Huabei Liu; Jie Wang; Wen Liu; Lili Xie (Soil Dynamics and Earthquake Engineering, 2026)

Study on the Bioavailability of Arsenic in the Rice–Crayfish Farming System - Kelei Zhang; Shoudong Zhang; Longjun Deng; Tiancai Li; Li Liu; Wei Luo; Yibo Zhang; Yongyao Guo; Dan Liu; Shiyong Yang; Jun Wang; Dongjie Wang; et al. (Fishes, 2025)
Rice–fishery integrated farming has expanded rapidly in China, yet its implications for arsenic (As) accumulation remain insufficiently understood. This study evaluated As bioavailability and enrichment in a rice–crayfish farming system (RCFS) by establishing controlled field plots with soil As concentrations ranging from 5 to 40 mg/kg under three water-management regimes: alternating wetting and drying (AWD), continuously flooded (CF), and RCFS. Soil–water physicochemical variables and As accumulation in both rice organs and crayfish tissues were systematically analyzed, followed by human health risk assessment. Inorganic As in brown rice increased linearly with soil As, following Y = 0.0117X + 0.0598 (R2 = 0.96), and the estimated soil safety thresholds were 26.48 mg/kg for AWD, 11.98 mg/kg for RCFS, and 9.24 mg/kg for CF. AWD consistently exhibited the lowest As risk due to its ability to elevate soil Eh and maintain a more favorable pH, thereby suppressing As mobilization. Compared with CF, RCFS reduced As bioavailability through crayfish-induced bioturbation, which increased Eh, enhanced SOM and CEC, and improved soil aeration. As accumulation in crayfish tissues also rose with soil As, with abdominal muscle As fitting Y = 0.0085X + 0.0553 (R2 = 0.8588). Although abdominal muscle met safety limits, the hepatopancreas accumulated substantially higher As and exceeded carcinogenic risk thresholds, even at 5 mg/kg of soil As, indicating a potential health concern for consumers. This work elucidates As dynamics and enrichment mechanisms in RCFS, providing guidance for safer rice–crayfish production in As-impacted areas.

Biochar-Amended Composting Transforms Chicken Manure Waste Into a Resource: Enhancing Extra-Rhizosphere Soil Fertility and Shaping Microbial Communities - Longjun Chen; Haiping Fan; Lulong Zhong; Yuncai Wang; Cheng Chen; Xin Chen; Yanping Chen; Jiaolin Zhang; Yu Lin (Journal of Soil Science and Plant Nutrition, 2025)
This study elucidates the synergistic regulatory mechanisms of biochar-amended chicken manure and mushroom residue compost (BCM) on soil microbial communities and nutrient cycling in the extra-rhizosphere, while evaluating its potential for sustainable agricultural waste recycling. Methods: We conducted a 50-day composting trial using five biochar application rates (0–7%). Assessed parameters included compost maturity (C/N ratio), nutrient content (NO 3 − -N, available phosphorus [AP], soil organic matter [SOM]), phosphatase and catalase activities, microbial community composition, and metabolic pathways. We performed Redundancy analysis (RDA) to correlate SOM/AP dynamics with microbial diversity and functional pathways. Results: At 5–7% biochar, compost maturity improved significantly, with C/N ratios of 15.6–18.2 and 2.2-4.0-fold increases in NO 3 − -N (1.41 mg/g), AP (50.09 mg/kg), and SOM (166.11 g/kg). Enzymatic activities (phosphatase: 9.81 mg/g·24 h; catalase: 83.08 µmol/g·24 h) correlated strongly with SOM/AP (R 2 = 0.71–0.82). Biochar enriched Proteobacteria (34.1%) and Actinobacteriota (15.2%), suppressed Halophiles ( Halomonas reduced by 52%), and enhanced carbon metabolism and oxidative phosphorylation pathways. RDA identified SOM/AP as a key driver of microbial diversity (R 2 = 0.91). The 5% biochar dose optimized nutrient retention (37–59% increases in AP, Available potassium [AK], NO 3 − -N) while maintaining microbial diversity, outperforming higher doses. Conclusions: This study demonstrates biochar’s dual role in reshaping extra-rhizosphere microbial ecology and nutrient dynamics, offering a precision agriculture strategy for sustainable waste recycling and circular economy practices. The 5% biochar dosage proved optimal, enhancing nutrient cycling and microbial activity while mitigating halophilic microbial suppression. Graphical Abstract

The C2H2 Zinc-Finger protein ELR1 negatively regulates cytokinin metabolism and signaling pathway in rice - Zeyu Li; Shuyi He; Longjun Zeng; Guangzhong Zhang; Quan Wang (Functional & Integrative Genomics, 2025)

Superhydrophilic adsorptive nanofiber membranes for ultrafast and highly-efficient waterborne nanoplastic removal - Jingwen Zhou; Mi Zhou; Longjun Wang; Jiayu Tong; Xinhao Li; Jingru Zhou; Yuqian He; Linlin Yan; Xiquan Cheng (Journal of Hazardous Materials, 2025)

Scalable flexible evaporator with enhanced thermal localization for solar driven water-power cogeneration - Longjun Wang; Xiquan Cheng; Xiao Sui; Jingwen Zhou; Zhuolin Han; Jingru Zhou; Guoke Zhang; Yingjie Zhang; Jun Ma; Kai Wang (Chemical Engineering Journal, 2025)

How to improve enterprises’ responsiveness to green policies? Empirical evidence from multivariate policy scenario analysis - Liping Wang; Longjun Chen; Ting Zeng; Chuang Li (Environment, Development and Sustainability, 2025)

Modelling the impacts of climate change and harvesting on carbon dynamics in representative subtropical secondary forests: A case study from Hunan Province, China - Longjun Wang; Haoyun Liu; Zelin Liu; Tong Li; Peng Li; Ziying Zou; Xiaolu Zhou; Weifeng Wang; Changhui Peng; Wenhua Xiang; Cong Liu (Ecological Modelling, 2025)

High-density magnetic-carbon interfaces in NiCu@C heterojunction toward broadband electromagnetic wave absorption - Zhikai Yan; Mengqiu Huang; Longjun Rao; Wenbin You; Biao Zhao; Lei Wang; Limin Wu; Ruixuan Zhang; Wei Li; Renchao Che (Chemical Engineering Journal, 2025)

A comprehensive understanding of thermal tolerance in Percocypris pingi (Tchang, 1930) under different acclimation temperatures supported by behavioral assessments - Yongyao Guo; Tong Li; Li Liu; Tiancai Li; Longjun Deng; Siyi Zhu; Shun Zhong; Qingjie Wang; Dongjie Wang; Wei Luo; Zongjun Du (Journal of Thermal Biology, 2025)

Identifying different classes of geoacoustic events using machine learning - Jian Wang; Yujun Zuo; Longjun Dong; Xianhang Yan (International Journal of Rock Mechanics and Mining Sciences, 2025)

Case study on pre-warning and protective measures against rockbursts utilizing the microseismic method in deep underground mining - Longjun Dong; Xianhang Yan; Jiachuang Wang; Zhen Tang; Hongwei Wang; Wentang Wu (Journal of Applied Geophysics, 2025)

Spatiotemporal clustering of microseismic signals in mining areas: A case study of the Baoji lead‑zinc mine in Shaanxi, China - Jian Wang; Yujun Zuo; Longjun Dong; Xianhang Yan (Engineering Geology, 2025)

Bibliometric analysis of research on recycling dredged sediment as construction material during the past three decades: trends and focal points - Hongwei Wang; Jiahui Zhang; Dongxing Wang; Rachid Zentar; Lei Lang; Daoyuan Sun; Longjun Dong (Journal of Soils and Sediments, 2025)

Rock mass instability early warning model: A case study of a high and steep annular slope mining areas using Sen’s slope trend analysis - Jiachuang Wang; Longjun Dong; Shengyu Ji (Tunnelling and Underground Space Technology, 2025)

Golgi apparatus regulated pyroptosis through the miR-32-5p/Golga7/NLRP3 axis in chicken splenic lymphocytes exposure to ammonia - Jiahao Liu; Haifeng Liu; Haojinming Tang; Longjun Ran; Danni Wang; Falong Yang; Huanrong Zhang; Xiaohua Teng; Dechun Chen (Environmental Pollution, 2024)

Spatio-temporal evolution characteristics and spatial spillover effects of forest carbon sink efficiency in China - Liping Wang; Longjun Chen; Ying Long; Chuang Li (Environment, Development and Sustainability, 2024)

Effects of Co3O4 modified with MoS2 on microbial fuel cells performance - Jingyi Ye; Teng Zhang; Yu Hao; Wenwen Tan; Huaren Su; Yong Wang; Qi Feng; Longjun Xu (Journal of Environmental Management, 2024)

In situ mass spectrometry imaging reveals pesticide residues and key metabolic pathways throughout the entire cowpea growth process - Shufan Jiang; Jingling Lin; Rui Zhang; Qiong Wu; Hongxing Li; Qun Zhang; Mingyue Wang; Longjun Dai; Defang Xie; Yue Zhang; Xinzhong Zhang; Bingjun Han (Journal of Hazardous Materials, 2024)

Divergent contributions of spring and autumn photosynthetic phenology to seasonal carbon uptake of subtropical vegetation in China - Ying Peng; Peng Li; Xiaolu Zhou; Yunpeng Luo; Cicheng Zhang; Longjun Wang; Tong Li; Changhui Peng (Journal of Geographical Sciences, 2024)

Heterointerface engineering in porous microspheres for magnetic-dielectric balance to boost electromagnetic wave absorption - Longjun Rao; ZhuoLin Li; Yuetong Qian; Mengqiu Huang; Lei Wang; Yongsheng Liu; Jincang Zhang; Yuxiang Lai; Chongyun Liang; Renchao Che (Chemical Engineering Journal, 2024)

A novel ZnCo2O4/BiOBr p-n/Z-scheme heterojunction photocatalyst for enhancing photocatalytic activity - Tao Xiong; Qi Feng; Cimei Fang; Rui Chen; Yanxi Wang; Longjun Xu; Chenglun Liu (Environmental Science and Pollution Research, 2024)

Effect of hydrofluoric acid-modified Co3O4/Y-type molecular sieves on MFC performance - Yong Wang; Teng Zhang; Wenwen Tan; Jingyi Ye; Chenglun Liu; Qi Feng; Longjun Xu (Journal of Water Process Engineering, 2024)

Genotype diversity and antibiotic resistance risk in Aeromonas hydrophila in Sichuan, China - Kun Peng; Mengzhu Chen; Yilin Wang; Ziqi Tian; Longjun Deng; Tiancai Li; Yang Feng; Ping Ouyang; Xiaoli Huang; Defang Chen; Yi Geng (Brazilian Journal of Microbiology, 2024)

miRNA-146a-5p Inhibits Hypoxia-Induced Myocardial Fibrosis Through EndMT - Yan Wang; Jie Yu; Chunxia Ou; Yue Zhao; Lixing Chen; Wenke Cai; Huawei Wang; Shiying Huang; Jie Hu; Guihu Sun; Longjun Li (Cardiovascular Toxicology, 2024)

Integrative analysis of transcriptomic profile reveals potential roles of miRNAs in regulating development of Marsupenaeus japonicas - Jing Wang; Longjun Pu; Xiaojuan Zhang; Cuicui Liang; Dandan Dong; Jiantao Guan; Huarong Guo (Journal of Oceanology and Limnology, 2024)

High temporal and spatial resolution characteristics of evaporation, transpiration, and evapotranspiration from a subalpine wetland by an advanced UAV technology - Chunhua Yan; Jiao Xiang; Longjun Qin; Bei Wang; Zhe Shi; Weiyang Xiao; Muhammad Hayat; Guo Yu Qiu (Journal of Hydrology, 2023)

Grazing alters vegetation phenology by regulating regional environmental factors on the Tibetan Plateau - Longjun Wang; Peng Li; Tong Li; Xiaolu Zhou; Zelin Liu; Ziying Zou; Qiuan Zhu; Changhui Peng (Agriculture, Ecosystems & Environment, 2023)

Stable single iron atom within two-dimensional porphyrin sheet catalysis for CO oxidation: A computational investigation - Kefeng Xie; Shengyuan Xu; Kai Xu; Jie Wang; Longjun Ma; Jun-Bing Lin (Fuel, 2023)

Corrigendum to “Seasonal variation in water uptake patterns of two greening species and their responses to rainfall events in a subtropical megacity of China” [J. Hydrol. (2023) 129262] - Bei Wang; Chunhua Yan; Zhe Shi; Jinshan Ding; Tengran Zhang; Longjun Qin; Guo Yu Qiu (Journal of Hydrology, 2023)

The gravitational potential and its first- and second-order partial derivatives of an ellipsoidal tesseroid based on the Cartesian integral kernel - Shuai Wang; Zhaoxi Chen; Longjun Qiu (Studia Geophysica et Geodaetica, 2023)

An in-situ measurement and assessment of evaporative cooling effects of low impact development facilities in a subtropical city - Chunhua Yan; Junjie Ding; Bei Wang; Longjun Qin; Zhe Shi; Guo Yu Qiu (Agricultural and Forest Meteorology, 2023)

Seasonal variation in water uptake patterns of two greening species and their responses to rainfall events in a subtropical megacity of China - Bei Wang; Chunhua Yan; Zhe Shi; Jinshan Ding; Tengran Zhang; Longjun Qin; Guo Yu Qiu (Journal of Hydrology, 2023)

Visualization and metabolome for the migration and distribution behavior of pesticides residue in after-ripening of banana - Meiran Wang; Qiaoxia Tian; Hongxing Li; Longjun Dai; Yi Wan; Mingyue Wang; Bingjun Han; Huaping Huang; Yunuo Zhang; Juncheng Chen (Journal of Hazardous Materials, 2023)

Co-occurrence of genes for antibiotic resistance and arsenic biotransformation in paddy soils - Huiling Cui; Dong Zhu; Longjun Ding; Yifei Wang; Jianqiang Su; Guilan Duan; Yongguan Zhu (Journal of Environmental Sciences, 2023)

A review of energy extraction from wind and ocean: Technologies, merits, efficiencies, and cost - Shafiqur Rehman; Luai M. Alhems; Md. Mahbub Alam; Longjun Wang; Zakria Toor (Ocean Engineering, 2023)

Comparative transcriptome and adaptive evolution analysis on the main liver and attaching liver of Pareuchiloglanis macrotrema - Qing Wu; Xiaoyang Zhang; Jie Li; Longjun Deng; Dongjie Wang; Min Liao; Zhonggang Guo; Xiaoli Huang; Defang Chen; Yan Wang; Shiyong Yang; Zongjun Du; et al. (Journal of Applied Genetics, 2022)

The beneficial roles of poisonous skin secretions in survival strategies of the odorous frog Odorrana andersonii - Naixin Liu; Buliang Meng; Wenxin Bian; Meifeng Yang; Longjun Shu; Yixiang Liu; Zhe Fu; Yinglei Wang; Ying Wang; Xinwang Yang (The Science of Nature, 2022)

Expressional characterization of galacturonosyltransferase-like gene family in Eucalyptus grandis implies a role in abiotic stress responses - Longjun Cheng; Xiaoxiang Ni; Mi Zheng; Lijuan Sun; Xiaofei Wang; Zaikang Tong (Tree Genetics & Genomes, 2018)

Computational identification and characterization of microRNAs and their targets in Penaeus monodon - Longjun Pu; Jing Wang; Yu Wang; Jianwei Zuo; Huarong Guo (Journal of Oceanology and Limnology, 2018)

Characterization of porcine epidemic diarrhea virus infectivity in human embryonic kidney cells - Jian Zhang; Longjun Guo; Yunfei Xu; Lijun Yang; Hongyan Shi; Li Feng; Yue Wang (Archives of Virology, 2017)

Production of porcine TNFα by ADAM17-mediated cleavage negatively regulates porcine reproductive and respiratory syndrome virus infection - Ren Li; Longjun Guo; Weihong Gu; Xiaolei Luo; Jian Zhang; Yunfei Xu; Zhijun Tian; Li Feng; Yue Wang (Immunologic Research, 2016)

Three-dimensional water quality model based on FVCOM for total load control management in Guan River Estuary, Northern Jiangsu Province - Li Zhang; Weibo Lin; Keqiang Li; Jianming Sheng; Aihong Wei; Feng Luo; Yan Wang; Xiulin Wang; Longjun Zhang (Journal of Ocean University of China, 2016)

Quantitative trait locus analysis and fine mapping of the qPL6 locus for panicle length in rice - Lin Zhang; Jianjun Wang; Junmin Wang; Linyou Wang; Bin Ma; Longjun Zeng; Yongbin Qi; Qun Li; Zuhua He (Theoretical and Applied Genetics, 2015)

Removal of dissolved inorganic carbon in the Yellow River Estuary - Zhiyuan Liu; Longjun Zhang; Wei-Jun Cai; Liang Wang; Ming Xue; Xiangshang Zhang (Limnology and Oceanography, 2014)
The Yellow River of China runs mainly through an arid and semiarid midlatitude region that has experienced substantial anthropogenic and climatic change. This area includes the carbonate‐rich Loess Plateau and carries water of exceptionally high carbonate content. To investigate the processes by which dissolved inorganic carbon (DIC) is biogeochemically modified as the river approaches the sea, a multipronged field investigation was conducted in the Yellow River estuary, 2005–2009. The project included four research cruises (spring and fall), a year of monthly sampling at a lower‐river hydrological station (Lijin), and in situ bottle incubations. Our study revealed that 4–11% of the Yellow River DIC was removed from the water column in the estuarine mixing zone and thus was not transported to the sea. DIC removal was greater in the spring and occurred at a higher salinity range than in the fall. As a unique feature of the Yellow River estuary, calcium carbonate (CaCO 3 ) precipitation was nearly as important as net biological production in the DIC removal. Longer freshwater—seawater mixing distances (and times) and higher DIC concentrations in the freshwater end member also promoted net biological production and CaCO 3 precipitation, thus encouraging DIC removal.

Construction of Stress Responsive Synthetic Promoters and Analysis of Their Activity in Transgenic Arabidopsis thaliana - Lei Hou; Longjun Chen; Junyi Wang; Dongfang Xu; Lixin Dai; Hui Zhang; Yanxiu Zhao (Plant Molecular Biology Reporter, 2012)

Carbonate mineral saturation states along the U.S. East Coast - Li-Qing Jiang; Wei-Jun Cai; Richard A. Feely; Yongchen Wang; Xianghui Guo; Dwight K. Gledhill; Xinping Hu; Felipe Arzayus; Feizhou Chen; Justin Hartmann; Longjun Zhang (Limnology and Oceanography, 2010)
To assess the impact of ocean acidification on the carbonate chemistry of the shelf waters off the southeastern United States (South Atlantic Bight [SAB]), we measured carbonate mineral saturation states from January 2005 to May 2006. The findings reveal that aragonite (Ω arag : 2.6–4.0) and calcite (Ω cal : 4.1–6.0) saturation states were considerably higher than those recently reported along the West Coast of North America. Different water mass age between the Atlantic and Pacific Oceans during global ocean circulation is the primary reason for the higher carbonate mineral saturation states in the SAB than along the West Coast. The contrasting water temperatures in the two coasts contribute to such differences. Both upwelling and freshwater discharge also play important roles in controlling saturation state. Carbonate mineral saturation in the surface water of the West Coast is strongly controlled by the upwelling of high‐salinity, low‐temperature, low‐oxygen, and low‐pH deep water. In comparison, saturation states in the surface water of the SAB coast are rarely affected by upwelling. Instead, they are strongly influenced by the input of low‐saturation‐state water from rivers. Continued increases of atmospheric CO 2 under the Intergovernmental Panel on Climate Change B1 emission scenario will decrease the carbonate mineral saturation states by up to 40% by the end of this century, and aragonite will approach undersaturation near the coast.